Investigating Steps and Usage of Idioms in Linguistics and Sociology Research Articles - Prihantoro, Prihantoro; Mudeng, Hadassah Yael Leonard; Rahmah, Aisyah Tiara (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
In academic writing, as a background, a vast number of lexico grammatical patterns and idioms may be used. An issue for learners of academic writing, particularly beginners, is identification and usage. There might also be some differences between patterns and idioms used in one domain and another. Thus, we aim to identify and compare lexicogrammatical patterns and idioms used in English research articles in the MICUSP corpus, focusing on two fields: linguistics and sociology. As for the methods, we adopt Morley’s (2014) academic phrasebank to identify lexicogrammatical patterns as it categorises patterns following their academic writing functions, which we refer to as ‘steps’ such as establishing context, presenting an issue, stating the purpose, etc. In addition to several idioms databases, we use our introspection to recognize idioms used in the corresponding steps. As for the results, we discover that linguistics is superior in the frequency of step C3 (methods), which may be due to the need to explain several new techniques in more detail. However, sociology excels in using idioms whose reasons might need further investigation. This study has at least two implications, 1) new lexicogrammatical patterns and idioms can be incorporated into Morley’s phrasebank, and 2) students can instantly replicate them